You are on page 1of 72

Chap 3

Section 3.1

1
f ( x ) = x 3 x
3

Solution:

f ( x) = x 3 x
3

f '( x ) = 3 x 6 x
2

= 3 x ( x 2)
: x = 0, 2

2
g ( t ) = t 4 t , t < 3
Solution:

g(t ) = t 4 t , t < 3
1
1

1
g '( t ) = t[ (4 t ) 2 ( 1)] + (4 t ) 2
2

1
= (4 t ) 2 [ t + 2(4 t )]
2

8 3t
2 4t

8
: t =
3

3
h( x ) = sin 2 x + cos x , 0 < x < 2
Solution:

h( x ) = sin 2 x + cos x , 0 < x < 2

h '( x ) = 2sin x cos x sin x


= sin x (2cos x 1)

(0,2 )

5
: x = , ,
3
3

4
f ( x ) = 3 x ,[1, 2]
Solution:

f ( x ) = 3 x ,[1, 2]

f '( x ) = 1
:(-1,4)
:(2,1)

5
3 2
f ( x ) = x x ,[1, 2]
2
3

Solution:

3 2
f ( x ) = x x ,[1, 2]
2
3

f '( x ) = 3 x 2 3 x = 3 x ( x 1)
5
:(-1, )
2

: (2, 2)

1
:(0,0),(1,- )
2

6
t2
g( t ) = 2
,[1,1]
t +3

Solution:

t2
g(t ) = 2
,[1,1]
t +3
6t
g '( t ) = 2
( t + 3)2

: (0, 0)

1
:(-1, )
4
1
: (1, )
4

7
1
h( s ) =
,[0,1]
s2
Solution:

1
h( s ) =
,[0,1]
s2

1
h '( s ) =
( s 2)2
1
:(0,- )
2

:(1, 1)

8
1
f ( x ) = cos x ,[0, ]
6
Solution:

1
f ( x ) = cos x ,[0, ]
6

f '( x ) = sin x
:(0,1)
1 3
:(
)
6 2

Section 3.2 Rolle

1
f ( x ) = x 2 + 3 x ,[0, 3] f [a , b]
(a , b )
f '(c ) = 0 c
Solution:

f ( x ) = x + 3 x ,[0, 3]
2

f (0) = f (3) = 0

f '( x ) = 2 x + 3

3
2 x + 3 = 0 x =
2
f [0,3](0,3)
3
c :

2
2
3

f [a , b]

f ( x ) = x 1,[ 8, 8]

(a , b )
f '(c ) = 0 c
Solution:

2
3

f ( x ) = x 1,[ 8, 8]
f ( 8) = f (8) = 3

f '(0)
f [-8,8](-8,8)

3
f ( x ) = sin x ,[0, 2 ] f [a , b]
(a , b )
f '(c ) = 0 c
Solution:

f ( x ) = sin x ,[0, 2 ]

f (0) = f (2 ) = 0

f '( x ) = cos x

f [0,2 ] (0,2
) c : ,
2 2

4
f ( x ) = tan x ,[0, ] f [a , b]
(a , b )
f '(c ) = 0 c
Solution:

f ( x ) = tan x ,[0, ]

f (0) = f ( ) = 0

f( )
2

f [0, ]

5
f ( x ) = x 2 ,[2,1] f [a , b]
f (b) f (a )
(a , b )
f '(c ) =
c
ba

Solution:

f ( x ) = x 2[2,1]( 2,1)

f (1) f ( 2) 1 4
=
= 1
1 ( 2)
3

f '( x ) = 2 x = 1

1
x=
2
1
c=
2

6
f ( x ) = x 3 + 2 x ,[1,1] f [a , b]
f (b) f (a )
(a , b)
f '( c ) =
c
ba

Solution:

f ( x )[1,1](-1,1)

f (1) f ( 1) 3 ( 3)
=
=3
1 ( 1)
2

f '( x ) = 3 x + 2 = 3
2

3 x2 = 1
x=

1
3

3
c=
3

7
2
3

f ( x ) = x ,[0,1] f [a , b]

f (b) f (a )
(a , b )
f '(c ) =
c
ba

Solution:

f ( x )[0,1](0,1)

f (1) f (0)
=1
1 0

2 3 8
x=( ) =
3
27

2 13
f '( x ) = x = 1
3

8
c=
27

8
f ( x ) = sin x ,[0, ] f [a , b]
f (b) f (a )
(a , b )
f '(c ) =
c
ba

Solution:

f ( x ) [0, ] (0,
)
f ( ) f (0) 0 0
=
=0
0

f '( x ) = cos x = 0

x=
2

c=
2

Section 3.3

1
g ( x ) = x 2 2 x 8
Solution:

< x < 1 1 < x <

g( x ) = x 2 x 8
2

g '( x ) = 2 x 2

: x = 1

g' < 0

g' > 0

: (1, )
: (- ,1)

2
f ( x ) = sin x 1, 0 < x < 2
Solution:

f ( x )= sin x 1, 0 x<
f '( x ) = cos x
3
: x = ,
2 2

0< x<
2
2 <
f '> 0

3 3
<x<
< x < 2
2
2
2
f '< 0
f '> 0

3
: (0, ),( , 2 )
2
2
3
: ( ,
)
2 2

3
f ( x) = x 4 x
2

- < x < 2 2 < x <

Solution:

f ( x) = x 4 x
2

f '( x ) = 2 x 4

: x = 2

f '< 0

f '> 0

: (2, )
: ( , 2)

4
x5 5 x
f ( x) =
5

Solution:

x5 5 x
f ( x) =
5
f '( x ) = x 4 1

: x = -1,1

< x < 1 1 < x < 1 1 < x <


f '> 0
f '< 0
f '> 0

: ( , -1),(1, )
: ( 1,1)

5
1
3

f ( x ) = x + 1
Solution:
1
3

f ( x) = x + 1
1 23
1
f '( x ) = x =
2
3
3x3

: x = 0

< x < 0 0 < x <


f '> 0
f '> 0

: ( , )

6
f ( x) = 5 x 5

Solution:

< x < 5 5 < x <

f ( x) = 5 x 5
x5
f '( x ) =
=
x5
: x = 5

1, x < 5
1, x > 5

f '> 0

f '< 0

: ( , 5)

: (5, )

7
x2
f ( x) = 2

x 9
Solution:

x2
f ( x) = 2
x 9

< x < 3 3 < x < 0 0 < x < 3 3 < x <

f '> 0
( x 2 9)(2 x ) ( x 2 )(2 x )
f '( x ) =
( x 2 9) 2

18 x
( x 2 9)2

: x = 0 , 3

f '> 0

f '< 0
f '< 0

: ( , 3),( 3, 0)
: (0, 3),(3, )

8
f ( x) =

4 x 2 , x 0
2 x , x > 0

Solution:

f ( x) =

f '( x ) =

{
{

4 x , x 0
2 x , x > 0

2 x , x 0
2, x > 0

: x = 0

< x < 0 0 < x <


f '> 0

f '< 0

: ( , 0)

: (0, )

Section 3.4

1
y = x x 2
2

Solution:

y = x2 x 2

y' = 2x 1

y" = 2
: ( , )

2
f ( x ) = x 3 + 6 x 2 9 x 1
Solution:

f ( x) = x + 6 x 9 x 1
3

f '( x ) = 3 x 2 + 12 x 9

: ( , 2)

f "( x ) = 6 x + 12 = 6( x 2)

: (2, )

3
24
f ( x) = 2
x + 12

Solution:

24
f ( x) = 2
x + 12
48 x
f '( x ) = 2
( x + 12)2

144(4 x 2 )
f "( x ) =
( x 2 + 12)3

: ( , -2),(2, )

: (-2, 2)

4
y = 2 x tan x ,(


, )
2 2

Solution:


y = 2 x tan x ,( , )
2 2

y ' = 2 sec x
2

y " = 2sec x tan x


2

: ( , 0)
2

: (0, )
2

5
f ( x ) = ( x 5)2
Solution:

f ( x ) = ( x 5)2

: x = 5

f '( x ) = 2( x 5)

f "(5) > 0

f "( x ) = 2

,(5, 0)

6
f ( x) =

x2 + 1

Solution:

f ( x) =

f '( x ) =
f "( x ) =

x2 + 1

: x = 0

x
x2 + 1
1
( x 2 + 1)

3
2

f "(0) = 1 > 0

,(0,1)

7
1
f ( x) =
x 1
Solution:

1
f ( x) =
x 1
1
f '( x ) =
( x 1)2

x = 1

8
f ( x ) = cos x x ,[0, 4 ]

Solution:

f ( x ) = cos x x ,[0, 4 ]
f '( x ) = sin x 1 0

,f

Section 3.5

1
3
lim(4 + )
x
x

Solution:

3
lim(4 + ) = 4 + 0 = 4
x
x

2
5 x
lim ( )
x x
3
Solution:

5 x
lim ( ) = ( )
x x
3

3
2x 1
lim
x 3 x + 2

Solution:

1
2( )
2x 1
20 2
x
lim
= lim
=
=
x 3 x + 2
x
2
3+ 0 3
3+( )
x

4
5 x2
lim

x x + 3
Solution:

5 x2
lim
= lim
x x + 3
x

5x
= ()
3
1+ ( )
x

5
lim

3 x + 1
x +x
2

Solution:

1
1
3 +
3( )
3 x + 1
x = lim
x =3
lim
= lim
x
x
1
x 2 + x x x 2 + x
1+ ( )
(
)
x
x2

6
x2 1

lim
x 2 x 1
Solution:

x2 1

1
2
2
x2 1
1
x
x
lim
= lim
= lim
=
x 2 x 1
x
x
1
1
2
2
2
x
x
1

7
1
lim
x 2 x + sin x

Solution:

1
lim
=0
x 2 x + sin x

8
1
lim cos( )
x
x
Solution:

1
lim cos( ) = cos 0 = 1
x
x

Section 3.6

x2 + 1
y= 2

x 4
Solution:

x2 + 1
y= 2
x 4
x = 0, y ' =

10 x
=0
( x 2 4)2

10(3x 2 +4)
x = 0, y" =
<0
2
3
( x 4)

,(0, )
4

2
x3

f ( x) =
x
Solution:

f ( x) =

x3
3
= 1
x
x

3
x 0, f '( x ) = 2 > 0
x
6
f "( x ) = 3 0
x

3
8
g( x ) = x 2
x

Solution:

8
x3 8
g( x ) = x 2 =
x
x2

x 3 + 16
x = 16, g '( x ) =
=0
3
x
3

x 0, g"( x ) =

-48
<0
4
x

( 3 16,-3 3 2 ) (-2.52,-3.78)

4
2
3

y = 3x 2x

Solution:

x = 1 x
=0
y' = 2x

1
3

2=

1
3

2(1 x )
x

x 0, y " =

1
3

3x

4
3

=0

5
y = 2 x x

Solution:

y = 2 x x3
y ' = 1 3 x 2

x = 0, y " = 6 x = 0

6
y = 2x 3

Solution:

y = 2x 3
y' =

2(2 x 3)
3
x =
2x 3
2

y" = 0

7
f ( x )= 2 x 4 sin x , 0

x
2

Solution:

f ( x ) = 2 x 4 sin x , 0 x 2
f '( x ) = 2 4 cos x

f "( x ) = 4sin x
1
f '( x ) = 0 cos x =
2

5
x = ,
3 3

f "( x ) = 0 x = 0, , 2
2
: ( ,
2 3)
3 3
5 10
:(
,
+2 3)
3
3

y = 2 x tan x , < x <


2
2

Solution:

y = 2 x tan x , < x <


2
2

x = , y ' = 2 sec 2 x =0
4

x = 0, y" = 2 sec2 x tan x=0


: ( , -1)
4 2
: (-

,1- )
4
2

Section 3.7

1
4
(
)
h

I
I = k(sin ) / s2
S k

1
Solution:

1
Solution:

V1
V2
sin 1 sin 2
1 2
=
v1
v2
Q

2
Solution:

sin
sin 2
1 =
v1
v2

1
2
V
1 V
2
P
Q

3
Solution:

Section 3.9

1
dy
y = 3 x 2 4
Solution:

y = 3x 4
2

dy = 6 xdx

2
x+1
y=
2x 1

dy

Solution:

x+1
y=
2x 1

3
dy =
dx
2
(2 x 1)

3
y = 9 x2

dy

Solution:

y = 9 x

1
dy = (9 x 2 ) 2 ( 2 x )dx =
2

x
9 x

dx

4
y = x 1 x2

dy

Solution:

y = x 1 x2
dy = ( x

x
1 x2

+ 1 x 2 )dx =

1 2 x2
1 x2

dx

5
y=

x+

1
x

dy

Solution:

y=

dy = (

1
2 x

x+

1
x

1
2x x

)dx =

x 1
2x x

dx

6
y = 3 x sin 2 x
dy
Solution:

y = 3 x sin x
2

dy = ( 3 2 sin xcos x) dx ( 3 =sin 2 x) dx

7
y = x cos x

dy

Solution:

y = x cosx
dy = ( xsin x cos
+ x) dx

8
1
6 x 1
y = cos(
)
dy
3
2
Solution:

1
6 x 1
y = cos(
)
3
2
6 x 1
dy = sin(
)dx
2